Economic Valuation of Nontimber Forest Products under the Changing Climate in Kilombero District, Tanzania - Chelestino Balama; Suzana Augustino; Danford Mwaiteleke; Leopord P. Lusambo; Fortunatus B. S. Makonda (International Journal of Forestry Research)
Sustainable collection of Nontimber Forest Products (NTFPs) for trade is an appropriate measure to increase people’s adaptive capacity against adverse effects of climate change. However, information on the economic value for NTFPs for subsistence use and trade under the changing climate is inadequate, particularly in households around Iyondo Forest Reserve (IFR), in Kilombero District, Tanzania. The study identified and quantified NTFPs used for subsistence and trade, estimated its economic value, and examined factors influencing supply of NTFPs at household level. Data were collected through Focus Group Discussions, key informant interviews, questionnaire survey of 208 sample households, and spot market analysis to randomly selected NTFPs collectors, sellers, and buyers. The study identified 12 NTFPs used for subsistence and trade, which was evaluated in terms of the mean annual value per household. The mean annual value of the identified NTFPs ranged from TZS 4700 to 886 600. The estimated economic value of the studied NTFPs was TZS 51.4 billion (USD 36 million). The supply of NTFPs at household level was influenced by distance to the forest, change in forest management regime, seasonality, and change in rainfall pattern. NTFPs around IFR have high economic value which portrays the potential of developing them to enhance households’ adaptive capacity against climate change adverse effects.